LIPID HOMEOSTASIS PECULARITIES IN ISCHEMIC HEART DISEASE PATIENTS WITH HEART FAILURE SYMPTOMS, DIABETES MELLITUS 2 TYPE AND METABOLIC SYNDROME DEPENDING ON MEDICATION PECULIARITIES - Zalyubovskaya, E.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
91 patients have been examined to study the effectiveness of (ACE inhibitor) lysinoprile in various dosesincluding its combination with carvedilol β-blocker as a complex treatment in ischemic heart disease patients with hert failure symptoms, diabetes mellitus 2 type (D) and metabolic syndrome (MS). The conclusion has been made that doses of lysinopril and carvedilol as a complex therapy in ischemic heart disease patients with hert failure symptoms, diabetes mellitus 2 type (D) and metabolic syndrome (MS) has a definitely positive effect concerning normalization of general cholesterol level (CH), triglycerids (TG), cholesterol lipoproteid of low density (CH-LPLD). Increasing lysinoprile dose allows to improve the level of CH-LPLD and lipoproteids of very low density (CH-LPVLD), and carvedilol promotes the reduction of CH, TG, CH-LPLD, CH -LPVLD levels. Combination of lysinoprile 2,5-5,0 mg with carvedilol 37,5-50,0 mg permits to increase the level of CH lipoproteids of high density.